(untitled) (KONFERENSIYA, 2025)
Good translation involves more than just replacing words between languages. It requires an understanding of collocational patterns, which are common combinations of words that have established meanings. This article looks at how being aware of collocations affects translation accuracy. Using ideas from phraseological theory, corpus linguistics, and psycholinguistic models, the research explores how learners handle collocations during translation tasks. A mixed-methods approach was used, which included translation tests, surveys, and a detailed analysis of errors. The results indicate that learners who are more aware of collocations produce translations that are much more natural, accurate, and idiomatic. The cognitive findings suggest that collocations ease the mental workload by acting as stored multiword units. This study supports the need to include collocational training in translation education